Advancing Research on the Future of Work in the Age of Artificial Intelligence (AI) - Sarala, Riikka M.; Post, Corinne; Doh, Jonathan; Muzio, Daniel (Journal of Management Studies, 2025)
AbstractTechnological developments – particularly related to artificial intelligence (AI), machine learning, and digitalization – are disrupting the workplace in unprecedented ways, particularly in professional and knowledge‐intensive sectors. Scholars' views on the implications of these disruptions range from optimism and pessimism to scepticism. Disciplines vary in how extensively they have considered the implications of these technological developments. With much prior work focusing on the more macro‐level phenomena and effects, the role of institutions, organizations and individuals – as well as their interrelatedness – remains less examined. In this introductory article to the special issue, we discuss the scope, extent and new domains of change related to the Future of Work and, especially, to AI. We also reflect on the consequences of these changes as well as the related processes and mechanisms through which they will manifest. Then, we introduce and summarize the articles included in this special issue along the above dimensions. We conclude by reflecting on the overall contribution of the special issue and on future directions for examining the Future of Work from the perspective of management studies.